Domestication As A Criss-cross Between The Human And The Animal’s World. A Phenomenological And Naturalist Perspective - Martínez Bravo, Cristián (Resonancias. Revista de Filosofía, 2020)
Domestication is understood as a criss-cross between humans and animals. Phenomenologically speaking, this phenomenon is a case in which animals acquire certain human traits that arise from the mutual coexistence between animals and human beings. Science has shown a case of two orangutans, namely, Chantek and Puti, who acquired certain non-verbal language capacities from the exposition in different degrees to human contexts. Nonetheless, such capacities depended on the force and richness of the coexistence between animals and human beings. In this paper, I want to show how domestication, understood as a criss-cross between human and animal life, could have ontological and ethical consequences for the constitution of animal and human subjectivities depending on the force and richness of the mutual coexistence between both of them.